ANALISIS PERAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN PROFESIONALITAS GURU - Endang, Endang Sri Mulyani; Suherman, Suherman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this paper is to find out how educational supervision can improve teacher professionalism and the efforts that can be made to improve teacher professionalism. In this paper, qualitative methods are used by analyzing different literature studies. The results of the study indicate that educational supervision improves the quality of teacher professionalism. Principals also have an important role in improving teacher professionalism. They must be good consultants for teachers and help them solve problems or difficulties. In addition, principals are also expected to be able to provide input that can help teachers improve their professionalism.